2013
DOI: 10.3390/en6021009
|View full text |Cite
|
Sign up to set email alerts
|

Hydrate Formation/Dissociation in (Natural Gas + Water + Diesel Oil) Emulsion Systems

Abstract: Abstract:Hydrate formation/dissociation of natural gas in (diesel oil + water) emulsion systems containing 3 wt% anti-agglomerant were performed for five water cuts: 5, 10, 15, 20, and 25 vol%. The natural gas solubilities in the emulsion systems were also examined. The experimental results showed that the solubility of natural gas in emulsion systems increases almost linearly with the increase of pressure, and decreases with the increase of water cut. There exists an initial slow hydrate formation stage for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…Finding technological and technical solutions aimed to tackle with complex obstructions requires fundamental studies in the fi eld of phase transitions and hydrate growth kinetics in systems constituted by paraffi n deposits and water. However, an analysis of modern literature concerned with this problem demonstrated that studies of gas hydrates are concentrated on theoretical and experimental analyses of the thermodynamics and growth/dissociation kinetics of methane hydrates in water-oil emulsions of various compositions [3][4][5][6][7][8][9][10][11][12][13][14], with the processes of hydrate formation in natural gas mixtures in paraffi n and water deposits still remaining unstudied. Our communication presents data on the thermobaric conditions and kinetic of natural gas hydrate formation in systems composed in various proportions from commercial Asphaltene-Resin-Paraffin Deposits (ARPDs) of the paraffi nic type and water.…”
mentioning
confidence: 99%
“…Finding technological and technical solutions aimed to tackle with complex obstructions requires fundamental studies in the fi eld of phase transitions and hydrate growth kinetics in systems constituted by paraffi n deposits and water. However, an analysis of modern literature concerned with this problem demonstrated that studies of gas hydrates are concentrated on theoretical and experimental analyses of the thermodynamics and growth/dissociation kinetics of methane hydrates in water-oil emulsions of various compositions [3][4][5][6][7][8][9][10][11][12][13][14], with the processes of hydrate formation in natural gas mixtures in paraffi n and water deposits still remaining unstudied. Our communication presents data on the thermobaric conditions and kinetic of natural gas hydrate formation in systems composed in various proportions from commercial Asphaltene-Resin-Paraffin Deposits (ARPDs) of the paraffi nic type and water.…”
mentioning
confidence: 99%
“…Ruffine et al [16][17][18][19][20] focused on hydrate reservoir exploration and field production tests using different porous media or sediment systems. Boxall et al [21][22][23] reported on the mechanism of hydrate dissociation in stirring reactors. The hydrate dissociation rate can be enhanced by increasing the experimental temperature or decreasing the experimental pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Both properties can be determined accurately by calorimetry (Deschamps and Dalmazzone, 2009;Gupta etal., 2008). The results, found in the literature for gas hydrates at high pressures are, however, generally scarce and obtained by extrapolation or less accurate and more laborious techniques such as visual observation in PVT cells (Setzmann and Wagner, 1991;Ruffine et al, 2010;Xiang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%